The innovativeness of the Finnish high technology firms – The role of internal factors, cooperation, and the mobility of labour - Jaakko Simonen (European Regional Science Association (ERSA), 2005)
Innovation is the driving force of the economy and it is the most important factor to the competitiveness of firms. Firms' capability to innovate, introduce new products to the market and develop new production methods has a significant effect on their success in the domestic and international markets. The role of innovativeness is emphasised particularly in the industries with a high growth rate and rapidly developing technology. This paper investigates the innovativeness of Finnish high technology firms, more precisely their local business units, between 1996 and 2002. Innovativeness of local business units is measured in terms of their ability to introduce both product and process innovations. The role of internal and external factors on the innovativeness of local units is analysed by the means of the probit analysis. An important and novel feature of my paper is that our data provides a unique chance to evaluate the role of two important channels of technological diffusion, R & D cooperation between the firms and institutions and the inter-firm mobility of labour for the innovativeness of high technology establishments. Econometric results reveal that internal factors of local units affect their ability to introduce product and process innovations differently. I find evidence that R & D cooperation, both between firms and between firms and research institutions, can act as a significant catalyst for innovation activity. Moreover, our empirical findings give some evidence that worker inflows, and thereby technology diffusion from other firms, has an effect on the innovativeness of the high technology establishments.
Keywords: 330